PENERAPAN ASAS KELANGSUNGAN USAHA (BUSINESS GOING CONCERN) DALAM SISTEM HUKUM KEPAILITAN INDONESIA: Application of the Business Going Concern Principle in the Indonesian Bankruptcy Law System - Manangi, Izra Charistulus; Wicaksana, Arif (Faculty of Law, Universitas Trisakti, 2024)
One of the four principles stipulated by Law Number 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Debt Payment is the Business Continuity Principle. The concept of business continuity which is also called